2022
DOI: 10.1088/1402-4896/ac9dc5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of perovskite solar cell for enhancement of device performance using SCAPS-1D

Abstract: Perovskite solar cells are a pioneering photovoltaic technology that has signif-icantly improved performance in current years. The fundamental n-i-p planar het-erojunction structure of solar cells is structured and simulated in the present work. The device configuration Glass/ITO/WS2/CH3NH3PbI3/P3HT/Au was investigated using the Solar Cell Capacitance Simulator (SCAPS-1D) program. To increase the performance of the photovoltaic solar cell thickness, bandgap, doping concentration and temperature have been varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the past ten years, numerous investigators have conducted studies on perovskite solar cells (PSCs) and observed a substantial improvement in their PCE. The exceptional characteristics of these materials, such as a significantly high absorption coefficient, an adjustable band gap, an extended carrier diffusion length, enhanced carrier mobility, a reduced trap state density, a lower excitons binding energy, and a cost-effective processing method, have facilitated their achievement of this remarkable accomplishment. The typical perovskite composition is presented by the chemical formulation ABX 3 , wherein A represents an inorganic or organic cation (MA, FA/Cs) and B represents a heavy metal (Sn, Pb, Ge), followed by an X signifying a halide anion (Cl, Br, and I). The hybrid organic–inorganic perovskites have blazed a trail toward a more efficient light-harvesting material. PSC efficiency has now increased from 3% to 25.6%. The versatile frequency of the PSCs enables them to efficiently capture the light of varying frequencies in different layers, thereby enhancing PCE. …”
Section: Introductionmentioning
confidence: 99%
“…In the past ten years, numerous investigators have conducted studies on perovskite solar cells (PSCs) and observed a substantial improvement in their PCE. The exceptional characteristics of these materials, such as a significantly high absorption coefficient, an adjustable band gap, an extended carrier diffusion length, enhanced carrier mobility, a reduced trap state density, a lower excitons binding energy, and a cost-effective processing method, have facilitated their achievement of this remarkable accomplishment. The typical perovskite composition is presented by the chemical formulation ABX 3 , wherein A represents an inorganic or organic cation (MA, FA/Cs) and B represents a heavy metal (Sn, Pb, Ge), followed by an X signifying a halide anion (Cl, Br, and I). The hybrid organic–inorganic perovskites have blazed a trail toward a more efficient light-harvesting material. PSC efficiency has now increased from 3% to 25.6%. The versatile frequency of the PSCs enables them to efficiently capture the light of varying frequencies in different layers, thereby enhancing PCE. …”
Section: Introductionmentioning
confidence: 99%
“…Defect density is determined by the relation given below which provides information regarding the rate of carrier recombination. [ 24,25 ] R = np ni2τp(n+ni)+τp(normalp+pi)$$\textrm{ } R \textrm{ } = \textrm{ } \frac{n p \textrm{ } - \textrm{ } n_{i}^{2}}{\left(\tau\right)_{\text{p}} \left(\right. n + n_{i} \left.\right) + \left(\tau\right)_{\text{p}} \left(\right.…”
Section: Resultsmentioning
confidence: 99%
“…Defect density is determined by the relation given below which provides information regarding the rate of carrier recombination. [24,25]…”
Section: Impact Of Total Defect Density At Mote 2 /Pbs-tbai Interfacementioning
confidence: 99%
“…[12][13][14][15] More specically, the organic-inorganic perovskites have blazed a trail toward a highly efficient light-harvesting material and the PSC efficiency has now increased from 3% to 25.6%. [16][17][18][19][20] Because of the tunable frequency, the PCSs can absorb different light frequencies effectively in different layers, improving PCE. [21][22][23][24][25][26] Many previous studies have been conducted on perovskite materials consist of Pb, which are the most efficient and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…12–15 More specifically, the organic–inorganic perovskites have blazed a trail toward a highly efficient light-harvesting material and the PSC efficiency has now increased from 3% to 25.6%. 16–20 Because of the tunable frequency, the PCSs can absorb different light frequencies effectively in different layers, improving PCE. 21–26…”
Section: Introductionmentioning
confidence: 99%